(untitled) - Nefff, Stephen C. (Cambridge, UK, 2005)
This ambitious volume is a history of war, from the standpoint of international law, from the beginning of history to the present day. Its primary focus is on legal conceptions of war as such, rather than on the substantive or technical aspects of the law of war. It tells the story, in narrative form, of the interplay, through the centuries, between, on the one hand, legal ideas about war and, on the other hand, state practice in warfare. Its coverage includes reprisals, civil wars, UN enforcement and the war on terrorism. This book will interest historians, students of international relations and international lawyers.
Keywords: War ( international law ); History